Edukasi Penggunaan Memrise Dalam Meningkatkan Kemampuan Bahasa Inggris Pada Siswa Di SMK Bina Insan Siak Hulu - Nadila Permata Sari; Esti Raihana; Riyanti Nasution (Jurnal Masyarakat Mengabdi Nusantara, 2024)
English is an important language in the era of globalization. This article discusses the educational use of Memrise, an English language learning application, to improve the English language skills of Bina Insan Siak Hulu Vocational School students. Educational activities include counselling about the importance of English and an introduction to the Memrise application. The method used is the lecture method to convey the material. The results show that students know the importance of learning English, students understand the features and how to use the Memrise application. It is hoped that by studying and using the Memrise application students' English language skills can improve.